Penalising on the basis of the severity of the offence: A sophisticated revenue-based cartel penalty - Yannis Katsoulacos; Evgenia Motchenkova; David Ulph (Tinbergen Institute, 2017)
In Katsoulacos et al. (2015) we examined the welfare properties of a number of monetary penalty regimes for tackling cartels, including revenue-based penalties, the most widely used regime. We showed that for a typical industry overcharge–based penalties welfare-dominate the others. However these penalties are subject to criticisms on the grounds of high implementation costs and lack of transparency/uncertainty. In this paper we propose a new sophisticated revenue-based penalty regime in which the penalty base is the revenue of the cartel but the penalty rate increases in a systematic way with the cartel overcharge. Thus, the proposed regime formalises how revenue can be used as the base while taking into account the severity of the offence. We show that this hybrid regime can replicate the desirable welfare properties of overcharge-based penalties while having relatively low levels of implementation costs and of uncertainty, concluding that the proposed penalty regime deserves very serious attention from Competition Authorities.
Keywords: L4; K21; D43; 330; Antitrust Penalties; Antitrust Enforcement; Antitrust Law; Cartels